Experimental Study of the Benefits of a Second Antenna at the User Side in a Massive MIMO System - Alex Oliveras Martinez; Petar Popovski; Jesper Odum Nielsen; Elisabeth De Carvalho (IEEE Access, 2018)
Massive MIMO is commonly described as a large number of base station (BS) antennas serving a smaller number of single-antenna users. However, adding a second antenna to the user handset opens the possibility to exploit multiplexing techniques and obtain higher throughput. This paper is based on a measurement campaign comprising a BS with 64 elements reconfigurable into three shapes: 1) a very large array with 6-m aperture; 2) a large array with 2m aperture; and 3) a compact two dimensional array with 25 cm by 28 cm sides. We study the throughput in single-user and multi-user scenarios using both non-linear optimal and linear precoders. The experimental results show that the throughput increases when adding a second antenna, but the increase is lower than in Gaussian channels due to the intra-user correlation. However, increasing the number of BS antennas, massive MIMO achieves more benefits from the second antenna. A large number of users in the system and the inter-user correlation reduce the benefits of a second antenna in the user handset.